Non-Operative Management of Blunt Abdominal and Retroperitoneal Solid Organs Trauma, with Retroperitoneal Hemorrhage – Indications, Methodology and Necessity - V. V. Aleksandrov; S. S. Maskin; N. K. Yermolayeva; V. V. Matyukhin (Неотложная медицинская помощь, 2021)
Introduction. The article is devoted to an actual problem — blunt trauma of the abdomen and organs of the retroperitoneal space.Aim of study. Specify the indications for nonoperative management of patients with blunt trauma of the solid organs of the abdominal cavity, retroperitoneal space, with retroperitoneal hemorrhage and measures for this treatment option.Material and methods. The analysis of literature sources of Russian and foreign authors is carried out and the indications, methods and necessity of nonoperative management of patients with blunt trauma of solid organs of the abdominal cavity and retroperitoneal space, retroperitoneal hemorrhages are substantiated.Conclusion. Nonoperative management of patients with blunt trauma of solid organs of the abdominal cavity and retroperitoneal space, retroperitoneal hemorrhages is possible only in large specialized centers with a wide range of diagnostic and therapeutic capabilities.